Uji Aktivitas Ribosome Inactivating Protein (Rip) Pada Tiga -Spesies Familia Cucurbitaceae Trichosanthes Anguina L., Cucurbita Moschata Duch. DAN Citrullus Vulgaris Schrad - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ANBTRACT Ribosome Inactivating Protein (RIP) is a protein enzime which is produced by plants and act in ribosome there by inhibiting protein synthesis. This effect is caused by the RNA Nglycosidase activity that cleaves the glycosidic adenin4324 chain on 28S rRNA. The ability of RIP to cleave the supercoiled double stranded DNA in vitro have been reported, so this activity is used to identify the presence of RIP in plants. The detection of the RIP in seed of Pare Ular (Trichosanthes anguina L.), Labu Parang (Cucurbita nzoschata Duch) --and Semangka (Citrullus vulgaris Schrad.), was done by invitro cleavage of supercoiled double stranded DNA which was treated by crude extract sample, followed by N-glycosidase activity test from crude extract on Saccharomyces cerevisiae ribosome. Result showed that crude extract of Trichosanthes anguina, Cucurbita moschata, and Citrullus vulgaris cv. Sun Flower and Diana expressed an enzimatic activity. However, Citrullus vulgaris cv. Sun. Flower only cleaved of supercoiled double stranded. In conclusion the Trichosanthes anguina, Cucurbita moschata, and Citrullus vulgaris cv. Sun Flower and Diana seeds contain RIP.